2005
DOI: 10.1016/j.apor.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of breaking criteria of deepwater wind waves under strong wind action

Abstract: The present study describes an experimental investigation of breaking criteria of deepwater wind waves under strong wind action. In a wind wave flume, waves were generated using different wind speeds and measured at different locations to obtain wave trains of no, intermittent, or frequent breaking. Water particle movement and free surface elevation were measured simultaneously using a PIV system and a wave gauge, respectively. For wind waves, not all the waves measured at a fixed location are breaking waves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The accurate prediction of wave-breaking onset is challenging and has been the focus of many investigations. Numerous breaking criteria have been proposed through theoretical analysis, numerical simulations, laboratory experiments, and field observations (Nepf et al 1998, Wu & Nepf 2002, Oh et al 2005, Tian et al 2008. Based on the predicting parameters involved, they can be classified into three categories, i.e., geometric, kinematic, and dynamic breaking criteria.…”
Section: Wave-breaking-onset Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate prediction of wave-breaking onset is challenging and has been the focus of many investigations. Numerous breaking criteria have been proposed through theoretical analysis, numerical simulations, laboratory experiments, and field observations (Nepf et al 1998, Wu & Nepf 2002, Oh et al 2005, Tian et al 2008. Based on the predicting parameters involved, they can be classified into three categories, i.e., geometric, kinematic, and dynamic breaking criteria.…”
Section: Wave-breaking-onset Predictionmentioning
confidence: 99%
“…This suggests that U/C ≥ 1 may be only a sufficient but not necessary condition for the onset of wave breaking. Using a PIV system, Oh et al (2005) also evaluated kinematic breaking criteria for deep-water waves under strong wind forcing. The maximum U/C observed in their experiments was approximately 0.75, which led them to the conclusion that this kinematic criterion is inadequate for the prediction of breaking onset under wind action.…”
Section: Kinematic Breaking Criteriamentioning
confidence: 99%
“…However, Stansell and MacFarlane 5 reported U / C ഛ 0.95 for spilling breakers and U / C ഛ 0.81 for plunging breakers, which indicate that the kinematic criterion is in general unable to predict the onset of breaking. In addition, Oh et al 6 recently conducted experiments to examine breaking criteria for deep-water wind waves under strong wind action using a PIV system. They also concluded that the kinematic criterion is an inadequate predictor of breaking for wind waves under strong wind action.…”
Section: Introductionmentioning
confidence: 98%
“…where the empirical coefficients are taken as a = 2.25 and b = 0.5, respectively. Even if several studies have providing criteria to predict the onset of wave breaking (Nepf et al (1998), Wu and Nepf (2002), Oh et al (2005) and Tian et al (2008)), none of them has been universally accepted in practice. Geometric-based breaking formulations describe the limiting wave height in terms of the maximum wave steepness or the breaker depth index.…”
Section: Basic Principles Of Wave Breaking and Run-upmentioning
confidence: 99%